KEWAJIBAN SUAMI DALAM MEMBERIKAN PENDIDIKAN AGAMA KEPADA ISTRI SESUAI KOMPILASI HUKUM ISLAM PADA KELUARGA MUALAF DI DESA PLAJAN KECAMATAN PAKIS AJI KABUPATEN JEPARA - Ulum, Masrofi Bahrul; Wibowo, Muhammad Kurniawan Budi; Baehaqi, B (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
In Plajan Village, Pakis Aji District, there are many families of converts due to marriage. Non-Muslim prospective wives convert to Islam so that their marriage is legal and recognized by the state. The impact of marriage is the existence of rights and obligations that must be fulfilled by husband and wife. One of the obligations listed in the Compilation of Islamic Law article 80 paragraph 3 is to regulate the husband's obligation to provide religious education to his wife. This study aims to: (1) find out that converts' families know the rights and obligations listed in the Compilation of Islamic Law, (2) implementation of the husband's obligation to provide religious education, and (3) obstacles that become obstacles for husbands in carrying out the obligation to provide religious education to his wife in Plajan Village, Pakis Aji District. Research on this thesis uses a qualitative descriptive method. This research is a Field Research (field research) with data collection methods through interviews, observation, documentation and literature study, then the research data are analyzed by data reduction. The results of this study indicate that (1) The families of converts do not yet know the rights and obligations listed in the Compilation of Islamic Law, (2) In general, husbands have carried out their obligations in providing Islamic religious education regarding basic knowledge in Islamic religious teachings (3) Among Obstacles to husbands in providing religious education to wives are economic problems, limited knowledge and insight into Islamic teachings.